A Multi‐Responsive Cd–Viologen Complex: Photochromism, Photomodulated Fluorescence, and Luminescent Sensing. Issue 23 (20th June 2018) - Qiu, Xing‐Tai; Shi, Qing; Zhang, De‐Quan; Lin, Qing‐Feng; Sun, Yan‐Qiong
Abstract: By incorporating a viologen moiety into a framework, a multiresponsive 2D bilayered luminescent Cd–viologen complex {[Cd1.5 (Cebpy)(Hbtc)Cl]⋅H2 O}n, (1, Cebpy=1‐carboxyethyl‐4, 4'‐bipyridine, H3 Hbtc=1, 3, 5‐benzenetricarboxylic acid) has been synthesized. The reversible photochromism from light brown to dark bluish‐grey is implemented due to the favourable spatial stack of the electron donor and acceptor. The photochromic component of the organic linkers can modulate the luminescence of compound1 under irradiation by using a Xenon lamp. At the same time, compound1 shows a good potential in luminescent sensing for colored transition metal cations. Thus, multiphotofunctionality, viz . photoluminescence, photochromism as well as the derivate fluorescent responses to irradiation and colored transition metal cations have been combined in the Cd–viologen complex1, which is the first example in the Cd–viologen‐based photochromic hybrid materials. Abstract : 2D bilayered luminescent Cd–viologen complex exhibits the rare reversible photochromism, photomodulated fluorescence and luminescent sensing for colored transition metal cations.